Calculus of variations and nonlinear partial differential equations : lectures given at the C.I.M.E. Summer School held in Cetraro, Italy, June 27-July 2, 2005 - Ambrosio, Luigi ; Dacorogna, Bernard ; Marcellini, Paolo (Springer, 2017)
213p.